Application of wood vinegar coconut shell and NPK fertilizer to maintain sustainable agriculture of upland rice production - Yugi R Ahadiyat; Sapto Nugroho Hadi; Okti Herliana (Brawijaya University, 2018)
Objective of this study was to know the effect of NPK fertilizer and wood vinegar coconut shell on upland rice yield and, pest and disease intensity. Inpago Unsoed 1 was a main object in this study. Application of different dose of NPK as main plot viz. 50% and 100% recommended dose and concentration of wood vinegar coconut shell of ratio i.e. 1: 20, 1: 40, 1: 60, 1: 80 and 1: 100 were tested. Observation variables were number of panicle per hill, number of seed per hill, percentage of filled seed, seed weight per hill, weight of 1000 seeds and weight of seed per effective plot. Application of wood vinegar coconut shell with concentration of 1:20 improved grain yield of upland rice and reduced 50% NPK application, and suppress intensity of pest and disease.